2009
DOI: 10.1021/jf9017383
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis and Mechanism on the Inhibition of Chlorogenic Acid and Its Components against Porcine Pancreas α-Amylase Isozymes I and II

Abstract: Chlorogenic acid (5-caffeoylquinic acid, 5-CQA) is a kind of polyphenol and is richly included in green coffee beans. The inhibitory effects of 5-CQA and its components, caffeic acid (CA) and quinic acid (QA), on the two porcine pancreas alpha-amylase (PPA) isozymes, PPA-I and PPA-II, were investigated using p-nitrophenyl-alpha-D-maltoside as substrate at pH 6.9 and 30 degrees C. The inhibition potencies of the respective inhibitors against both PPA isozymes were almost the same and in the order of 5-CQA > CA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 34 publications
1
81
1
Order By: Relevance
“…Therefore CS can be regarded as biomass which is expected to be utilised. Many investigators have reported the physiological functions of green and roasted coffee beans, such as a-amylase inhibition (Narita & Inouye, 2009, tyrosinase inhibition (Iwai, Kishimoto, Kakino, Mochida, & Fujita, 2004), and antioxidant activity (Richelle, Tavazzi, & Offord, 2001), etc. On the other hand, the physiological functions of CS reported until now are antioxidant activity (Borrelli, Esposito, Napolitano, Ritieni, & Fogliano, 2004), previotic property (Borrelli et al, 2004), and hyaluronidase inhibition (Furusawa, Narita, Iwai, Fukunaga, & Nakagiri, 2011), but the number of the reports is much less than that for coffee bean.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore CS can be regarded as biomass which is expected to be utilised. Many investigators have reported the physiological functions of green and roasted coffee beans, such as a-amylase inhibition (Narita & Inouye, 2009, tyrosinase inhibition (Iwai, Kishimoto, Kakino, Mochida, & Fujita, 2004), and antioxidant activity (Richelle, Tavazzi, & Offord, 2001), etc. On the other hand, the physiological functions of CS reported until now are antioxidant activity (Borrelli, Esposito, Napolitano, Ritieni, & Fogliano, 2004), previotic property (Borrelli et al, 2004), and hyaluronidase inhibition (Furusawa, Narita, Iwai, Fukunaga, & Nakagiri, 2011), but the number of the reports is much less than that for coffee bean.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study (Narita and Inouye, 2009;Narita and Inouye, 2011), we investigated the inhibition of porcine pancreas alpha-amylase (PPA) isozymes PPA-I and PPA-II by 8 types of cinnamic acid derivatives in green coffee beans. All CQAs, FQAs, and diCQAs showed mixed-type inhibition against PPA with K i > K i ′, indicating that these compounds bind to the enzyme-substrate complex more tightly than to the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Hanhineva et al [21] extensively reviewed the literature concerning polyphenol effects on inhibition of α-amylase [22], α-glucosidase [23] and glucose transporter activity in the gut [24]; protection of pancreatic cells from cytokine toxicity and effects on insulin release [25]; improved glucose uptake into tissues [26]; induction of hepatic glucokinase activity [27]; inhibition of gluconeogenesis [28]; and activation of adenosine monophosphate-activated protein kinase [29].…”
Section: Introductionmentioning
confidence: 99%